Pengaruh Flexible Working Space Dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Bank Syariah Indonesia Tbk. Kcp Padang Bypass - Afdhal Cassady Heru; Fiko Farlis (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to test and analyze flexible working space, work discipline and employee productivity on PT Bank Syariah Indonesia KCP Padang BYPASS. The sampling technique in this study used non probability sampling saturated sample technique. The research sample consisted of 22 respondents. Processing of research data using IBM SPSS Statistic 25 through validity tests, reliability tests, classical assumption tests, multiple linear analysis for hypothesis testing. The results of this study state that the F test shows that flexible working space and work discipline have a significant positive effect on employee productivity at PT Bank Syariah Indonesia KCP Padang BYPASS. The results of the t test state that flexible working space has a significant negative effect on employee work productivity, and work discipline has a significant negative effect on employee work productivity partially at PT Bank Syariah Indonesia KCP Padang BYPASS.